The Role of Political Connections in the Relationship Between Managerial Ability and Fraudulent Financial Statements - Yahya Yeshua Ahmad; Bambang Subroto; Sari Atmini (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study seeks to prove empirical evidence regarding the effect of managerial ability on fraudulent financial statements.Design/Methodology/Approach: The population of this study was manufacturing firms listed on the Indonesia Stock Exchange in the 2017-2019 period. The data met the criteria of as many as 90 companies with a total of 270 observations. Then, hypothesis testing in this research used moderated regression analysis.Research findings: Study outcomes demonstrated that managerial ability positively impacted fraudulent financial statements. Furthermore, the positive influence of managerial ability on the fraudulent financial statement was weaker when the company was politically connected.Theoretical contribution/Originality: This study provides empirical evidence regarding the heterogeneity of managerial ability and political connections as predictors of fraudulent financial statements.Practitioner/Policy implication: The study result provides a reference for regulators to provide more effective oversight of companies with superior managerial capabilities and is politically connected.Research limitation/Implication: The limitations in this research can be considered to formulate further research related to variable measurement. In addition, no single measurement method can explain various conditions.